Pemetaan Kedalaman Laut Menggunakan Multibeam Echosounder, (MB1) di Perairan Punggur, Kepri - Dodi Prima Resda; Muhammad Zainuddin Lubis; Dirgan Timbang (JURNAL INTEGRASI, 2021)
This research was conducted in April 2018 at Punggur waters. The methods used were bathymetric and tidal survey which aimed at obtaining depth and position information in Punggur waters which play a role in supporting activities around Punggur waters. This research was done by performing generalization using the Multibeam Echosounder (MBES) System instrument. Tides know the dynamics or changes in sea level. Thus, a bathymetric and tidal survey are carried out simultaneously namely the tides in the bathymetry survey activities aiming as a reference depth field to determine the kind/type of tide and the height of sea level average MSL (Mean Sea Level) as a reference point (zero points) for elevation measurements. It is known that the Formzahl value is 1.35 so that the tide type in the waters around the port is mixed mainly diurnal tides. The corrected bathymetry measurement results with an MSL value of 1.35 meters which results in an accuracy of the depth value. This indicates that there is a change in the depth value in Punggur waters, Batam. The results showed that the depth value in Punggur waters ranged from 16 to 25 meters below sea level so that the depth or bathymetry value in these waters was not included in the continental shelf area, which explains the presence of sloping topography values. Keywords: Bathymetry, Punggur waters, tides, Multibeam Echosounder (MBES)